Promotion Strategies of Family Education Guidance Service in Chinese Community - Chencheng Li; Pei Wu; Luyan Teng (Nicolaus Copernicus University in Toruń, 2022)
To carry out family education is related to the vital interests of thousands of families, and it is the top priority of the national livelihood work. It has become an international consensus to provide family education guidance services based on communities to improve the level and quality of family education. However, at present, there are still serious problems in the work of family education guidance services in Chinese communities, such as the absence of a normalized policy guarantee system, the weakening of value consensus by the game of stakeholders, and the prominent contradiction between supply and demand of high-quality resources. To this end, the following promotion strategies are proposed: improving relevant policies and regulations and ensuring the working operation mechanism; guiding residents to participate deeply and balancing the demands of stakeholders; deepening the supply-side reform of resources and promoting the quality development of education.